2019
DOI: 10.3390/rs11111299
|View full text |Cite
|
Sign up to set email alerts
|

Cubesats Allow High Spatiotemporal Estimates of Satellite-Derived Bathymetry

Abstract: High spatial and temporal resolution satellite remote sensing estimates are the silver bullet for monitoring of coastal marine areas globally. From 2000, when the first commercial satellite platforms appeared, offering high spatial resolution data, the mapping of coastal habitats and the extraction of bathymetric information have been possible at local scales. Since then, several platforms have offered such data, although not at high temporal resolution, making the selection of suitable images challenging, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 24 publications
1
50
0
4
Order By: Relevance
“…The final corrected SDB produced robust depths up to the limit of the lidar surveys, with typical errors ≤0.4 m. These excellent results from Sentinel-2 compared favorably with those produced in relatively low turbidity water in south Florida [22,44], and in regions with transparent waters [10,18,20,30]. Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19]. Recent studies have already indicated the potential of multi-scene approaches in order to select the optimal scene or eliminate noise over clear waters [16,17,19,20].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The final corrected SDB produced robust depths up to the limit of the lidar surveys, with typical errors ≤0.4 m. These excellent results from Sentinel-2 compared favorably with those produced in relatively low turbidity water in south Florida [22,44], and in regions with transparent waters [10,18,20,30]. Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19]. Recent studies have already indicated the potential of multi-scene approaches in order to select the optimal scene or eliminate noise over clear waters [16,17,19,20].…”
Section: Discussionmentioning
confidence: 96%
“…Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19]. Recent studies have already indicated the potential of multi-scene approaches in order to select the optimal scene or eliminate noise over clear waters [16,17,19,20]. However, our temporal compositing strategy successfully reduced the turbidity impact without requirement of visual inspection, thereby enhancing SDB performance in an easy way.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations